MPV17L2 is required for ribosome assembly in mitochondria. Issue 13 (19th June 2014) - Dalla Rosa, Ilaria; Durigon, Romina; Pearce, Sarah F.; Rorbach, Joanna; Hirst, Elizabeth M.A.; Vidoni, Sara; Reyes, Aurelio; Brea-Calvo, Gloria; Minczuk, Michal; Woellhaf, Michael W.; Herrmann, Johannes M.; Huynen, Martijn A.; et al.
Abstract: MPV17 is a mitochondrial protein of unknown function, and mutations in MPV17 are associated with mitochondrial deoxyribonucleic acid (DNA) maintenance disorders. Here we investigated its most similar relative, MPV17L2, which is also annotated as a mitochondrial protein. Mitochondrial fractionation analyses demonstrate MPV17L2 is an integral inner membrane protein, like MPV17. However, unlike MPV17, MPV17L2 is dependent on mitochondrial DNA, as it is absent from ρ 0 cells, and co-sediments on sucrose gradients with the large subunit of the mitochondrial ribosome and the monosome. Gene silencing of MPV17L2 results in marked decreases in the monosome and both subunits of the mitochondrial ribosome, leading to impaired protein synthesis in the mitochondria. Depletion of MPV17L2 also induces mitochondrial DNA aggregation. The DNA and ribosome phenotypes are linked, as in the absence of MPV17L2 proteins of the small subunit of the mitochondrial ribosome are trapped in the enlarged nucleoids, in contrast to a component of the large subunit. These findings suggest MPV17L2 contributes to the biogenesis of the mitochondrial ribosome, uniting the two subunits to create the translationally competent monosome, and provide evidence that assembly of the small subunit of the mitochondrial ribosome occurs at the nucleoid.